2015
DOI: 10.1007/s00394-015-0836-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increased wholegrain consumption on immune and inflammatory markers in healthy low habitual wholegrain consumers

Abstract: Despite the dramatic increase in WG consumption, there were no effects on phenotypic or functional immune parameters, markers of inflammation or metabolic markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 46 publications
3
25
0
Order By: Relevance
“…These observations were consistent with 2 (30, 31) of 3 (30,31,35) previous studies that investigated the effects of WGs on gut microbiota. We did not observe a difference in the bacterial diversity or phyla between groups, which was in agreement with the other intervention trials that used WG wheat as the main source of WGs (31,67).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…These observations were consistent with 2 (30, 31) of 3 (30,31,35) previous studies that investigated the effects of WGs on gut microbiota. We did not observe a difference in the bacterial diversity or phyla between groups, which was in agreement with the other intervention trials that used WG wheat as the main source of WGs (31,67).…”
Section: Discussionsupporting
confidence: 82%
“…In relation to this, we showed a significant difference in the percentage of terminal effector memory T cells between WG and RG groups, which may have implied that there was an enhanced potential in the adaptive immune response to a recall antigen. A similar finding was reported by Ampatzoglou et al (35) who showed a trend toward increased CD4 + terminal central memory cells in a WG group than in a control group. In addition, we showed that the LPSstimulated TNF-a production was significantly better maintained in the WG group that in the RG group.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations